Beyond government? the appeal of public-private partnerships - Boase, Joan Price (2000)
For the most part, the considerable literature devoted to new public management and its subset, alternative service delivery, is enthusiastic about this dramatic shift in the role of government. The metaphor of governments steering and the private sector rowing is an appealing one that has captured the imagination of many public officials and private-sector actors. Literature addressing this phenomenon tends to focus on defining the characteristics of various forms of government/private-sector partnerships rather than on assessing the implications and results of actual examples. This paper attempts to complement the existing literature by examining six cases of public-private partnerships, of both high and low prifile - the Confederation Bridge; the Charleswood Bridge; CANARIE; RCMP/Disney; Highway 407; and Chrysler/University of Windsor. The higher profile (and more costly) ventures have placed heavy emphasis on confidentiality, which raises concerns about traditional public-sector values such as accountability, democracy and neutrality. The conclusions of the article are mixed, but at the very least, they suggest the need for caution, vigilance and scepticism. - Reproduced
Keywords: Public administration